Investigating student’s misconception in solving mathematics problems using four-tier diagnostic test - Hanifah, Nurul; Fa’ani, Arini Mayan (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3616, 2024)
Misconceptions are a significant challenge in mathematics learning, indicated by students' misconceptions that do not align with scientific concepts. This mismatch often occurs in the One Variable Linear Inequality (PtLSV) material. This study aims to diagnose and analyze in depth the types of misconceptions (theoretical, classificational, and correlational) experienced by seventh-grade students of MTsN Kota Batu when solving PtLSV problems. This study uses a qualitative approach with a case study type. The main instruments used are a four-tier diagnostic test to select subjects and in-depth task-based interviews to explore the reasons behind the answers. A total of 61 students were tested, and 32 students (approximately 52.5%) were identified as having misconceptions. After further analysis of the 32 students who had misconceptions, 14 students (43.75%) had theoretical misconceptions, 10 students (31.25%) had classificational misconceptions, and 8 students (25%) had correlational misconceptions. Then, six students (two for each type of misconception) were selected as interview subjects. The results showed that students with theoretical misconceptions misinterpreted definitions or symbols, students with classificatory misconceptions categorized and modeled variables incorrectly, while students with correlational misconceptions made errors in algebraic conceptual relationships.